The Influence of Promotions on Purchase Decision Through Brand Image as a Mediation Variable: Study at The Semprit RIHO Cake Factory - Sari, Diyana Permata; Usdek, Dicky Wisnu; Putri, Viajeng Purnama (Universitas Muhammadiyah Malang, 2024)
This study aims to determine the effect of promotion on purchasing decisions through brand image as a mediating variable. The sampling technique uses accidental sampling. This research was conducted on consumers of the Semprit factory